Sustainability of Technology Use in Higher Education in Indonesia Post the COVID-19 Pandemic: Analysis of Scientific Evidence - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2022)
We carried out this study to analyze several scientific pieces of evidence on the sustainability of the use of technology in the context of post-pandemic higher education learning. We got several kinds of literature in the form of scientific evidence from several publications released between 2010 and 2020, which we obtained electronically with keyword-based searches such as “technology uses,